Minthostachys verticillate essential oil alone or micro encapsulated activates TH1 cells and induces the production of opsonizing antibodies - Campra, Noelia Anahí (2020)
In a previous study, we demonstrated the adjuvant capacity of theMinthostachys verticillata essential oil (EO) (2.5 mg/ml) or microencapsulated essential oil (EOMC) (5 mg/ml) on the humoral andcellular immune response against Enterococcus faecium in Balb/cmice. The aim of this study was to evaluate the functionality of thespecific antibodies produced and to quantify the IFN-γ and IL-4cytokines. Balb/c mice (n=4 per group) were inoculated by subcutaneous injection (days 0, 14 and 28) as follows: Group 1: 100 µlsaline solution; Group 2: 100 µl bacterin+EO (2.5 mg/ml); Group 3:100 µl bacterin+ microcapsule wall material (2.5 mg/ml); Group 4:100 μl bacterin+EOMC (5 mg/ml). In all groups, bacterin was of E.faecium. Seven days after the last booster, blood was obtained andserum was separated. Mice were sacrificed by cervical dislocationand spleens were removed to obtain splenic lymphocytes for cellproliferation assay. To evaluate the functionality of the antibodies,the Opsonophagocytic Killing Assay was carried out using different dilutions of the sera (1/100, 1/200, 1/500, 1/1000, 1/2000), E. faecium (1x107 CFU/ml), bovine PMNs (1x107cells/ml) suspensionsand a source of bovine complement. Sera antibodies of mice fromGroup 4 mediated the opsonization of E. faecium and enhance thephagocytosis by PMNs up to the 1/500 dilution compared to Group2, which was up to the 1/200 dilution (p<0.001). IFN-γ and IL-4 werequantified in the culture supernatants by sandwich ELISA. Higherlevels of IFN-γ and IL-4 were detected in lymphocyte culture supernatants of Group 2 compared to other groups (p<0.001). In Group 2,IFN-γ levels were higher than IL-4 (p<0.001), indicating that the activation of CD4+ T cells by the vaccine formulation containing aloneEO may result in a Th1 profile. The results obtained confirm thatEO and EOMC activate humoral and cellular immunity and could becandidates for vaccine adjuvants